A Pragmatic Analysis of Bullying in Emily Bronte Wuthering Heights - Iman Noori Jassim; Hadeel Mahmoud Ibrahim; Abudulqadir Talip Naeem; Taif Saad; Abeer Ali (RES MILITARIS, 2022)
The harmful nature of bullying is widely acknowledged by those who have direct experience with it, and this perception is intrinsically linked to the meaning and goals of bullying behavior. As a result of its detrimental effects on its targets, bullying consistently garners media and public attention. The study aims at: explaining the most dominant strategies of impoliteness within bullying extracts of Wuthering Heights and examining the purpose and implicated function behind using such utterances in Wuthering Heights. The current study adopts a qualitative method for analyzing twenty-three extracts by applying Culpeper’s (1995) Impoliteness and Grice’s (1978) implicature theories, besides Innes (2019) the functions of bullying. The study finds out that bald on record strategy of impoliteness has a high percentage (47.8%), and implicature of power is the most prominent feature within bullying utterances extracted from Bronte’s Wuthering Heights (scored 43.4%). Using "bald on record" more than other strategies shows that the authors do not care about the bullied person, since they have not used the less offensive strategies to show how bullying happens. The implicature of power is the most proposed and prominent one throughout the bullying utterances since the continual straggling to gain power between the two opposite sons of Earnshaw is the real reason of bulling most the time.